INTEGRASI NILAI-NILAI ISLAM DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN: MENGKAJI PERAN PENDIDIKAN UNTUK MEMBENTUK GENERASI BERKARAKTER DI TENGAH TANTANGAN GLOBALISASI - Mahmudah (Adisam Publisher, 2025)
This study aims to examine the integration of Islamic values in cultural history education and its role in shaping character-building generations amid the challenges of globalisation. Through literature analysis and a qualitative approach, this study found that Islamic values such as noble character, honesty, responsibility, and tolerance can be internalised in cultural history education. Amidst the onslaught of globalisation, which presents various challenges such as materialism and individualism, education based on Islamic values serves as a bulwark to preserve cultural and religious identity. The results of this study indicate that the integration of Islamic values in cultural history education not only enriches students' knowledge but also shapes a strong, principled, and adaptable personality in the face of global change. Thus, education that prioritises Islamic values plays a crucial role in nurturing a generation capable of harmoniously blending Islamic traditions with global dynamics.